FENOMENA KOMUNIKASI INTERPERSONAL MAHASISWA DALAM PERMAINAN JUDI ONLINE - Setyawan, Agus; Wangi, Maya Sekar; Itasari, Andri Astuti (Solidaritas, 2024)
This study aims to explore the impact of online gambling on social relationships amonguniversity students. Online gambling has become a global phenomenon affecting variousaspects of life, including social relationships among students. The study employs a surveymethod to collect data from students involved in online gambling, along with in-depthinterviews to understand the social impacts they experience. The findings indicate that onlinegambling can lead to a decline in the quality of interpersonal relationships, social isolation,and emotional stress. Factors such as lack of social support and environmental influencesexacerbate these effects. Based on these findings, it is recommended that educationalinstitutions enhance awareness through seminars and educational programs, providecounseling services, tighten regulation of online gambling access, and promote positiveactivities as alternative forms of entertainment. These measures are expected to mitigate thenegative impacts of online gambling and improve the quality of social relationships amongstudents.Keywords: Interpersonal Communication, Impact of Gambling, Social Relations, CollegeStudents